2001
DOI: 10.1097/00007890-200110270-00019
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytokine Polymorphic Inheritance and in Vitro Cytokine Production in Anti-Cd3/Cd28-Stimulated Peripheral Blood Lymphocytes1

Abstract: Polymorphisms in IL-2, IL-6, IL-10, and IFN-gamma genes are associated with their protein production after anti-CD3/CD28 stimulation. The profound effect of the IL-2 gene polymorphism in homozygous individuals may serve as a marker for those that could mount the most vigorous allo- or autoimmune responses, or perhaps become tolerant more easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
232
0
11

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(254 citation statements)
references
References 39 publications
9
232
0
11
Order By: Relevance
“…Using purified monocytes ( Figure 1) and B cells (Figure 3), our results support the concept that individuals with the C allele both spontaneously and upon LPS stimulation produce higher levels of IL-10 as compared to individuals with the A allele in these cell types. Others have reported a similar phenomena using PBMCs and Con A, anti-CD3/CD28 or interferon-α as a stimulus [17,29,35,36]. Though not statistically significant, a slight increase in IL-10 production was observed in purified T cells from individuals with the C allele when stimulated with either PMA/ionomycin or anti-CD3/CD28 (Figure 2).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Using purified monocytes ( Figure 1) and B cells (Figure 3), our results support the concept that individuals with the C allele both spontaneously and upon LPS stimulation produce higher levels of IL-10 as compared to individuals with the A allele in these cell types. Others have reported a similar phenomena using PBMCs and Con A, anti-CD3/CD28 or interferon-α as a stimulus [17,29,35,36]. Though not statistically significant, a slight increase in IL-10 production was observed in purified T cells from individuals with the C allele when stimulated with either PMA/ionomycin or anti-CD3/CD28 (Figure 2).…”
Section: Discussionsupporting
confidence: 55%
“…Many of these studies have relied on whole cell blood cultures or partially purified peripheral blood mononuclear cells stimulated with lipopolysaccharide to observe this effect [27,28]. Others have used purified T cells and stimulated with concanavalin A or anti-CD3/CD28 with mixed results in terms of IL-10 production [17,29]. In the present study, we analyzed IL-10 production from highly enriched populations of T cells, B cells and monocytes under various stimulation conditions in individuals either homozygous for the C or A allele at position -571 of the IL-10 promoter.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in concordance with data presented in a study on stimulated purified blood lymphocytes. 40 In this study, it was shown that the production of IL-10 was larger for subjects with the G allele compared with subjects with the A allele. Mö rmann et al 25 also found that the G allele was associated with a higher IL-10 production in mononuclear cells after LPS stimulation.…”
Section: Discussionmentioning
confidence: 61%
“…19,[25][26][27]32,40,41 Thus, Turner et al 27 found that subjects who were negative for the A allele exhibited a higher production of IL-10 than subjects who were positive for the A allele. These results are in concordance with data presented in a study on stimulated purified blood lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…177 Two small studies (no53) also failed to find a correlation between SNPs and TNF production. 178,179 Several larger studies have been conducted. A study by Huizinga et al 56 involving 179 subjects used a whole blood LPS stimulation assay, but found no statistical difference dependent on the 308 genotype.…”
Section: Ex Vivo Tnf Productionmentioning
confidence: 99%